Boudica’s Daughters: Conquest and Rape in the Ancient Roman Discourse - Lampinen, Antti (Säätiö Institutum Romanum Finlandiae, 2026)
It is well known that several of the stories told by the Romans about the earliest history of their polity pivoted on rape and sexual violence – both collectively, as in the case of the raptio of the Sabine Women, and individually, as in the case of Lucretia’s rape. Especially in Livy’s representation of the early Roman history rape is the catalyst for significant political upheavals. Issues of predestined rise to power, autocratic hubris, gendered virtue, and even “Roman” identity were all intertwined in these stories of male sexual violence. What is rather less frequently commented on, however, is the ethnic axis of the Roman narratives of conquest-as-rape and rape-as-conquest. To give but a single example, the topics of chapters in one collected volume from almost three decades ago jump straight from Livy to Byzantine princesses. The obvious omission of most of Roman history is striking. A recent volume on the strategy of the Roman Empire mentions “rape” only in the context of the Visigothic Sack of Rome. The image of Roman conquest as free of the sort of sexual violence and humiliation that we unfortunately still see in modern-day conflicts is strikingly sanitized. The connections between Roman imperialism, ethnic imaginaire and sexual violence are also relatively underexplored.This chapter will explore the intersection of the ethnic and the gendered in sources ranging from the later Republic to the late second century CE. The “embodied knowledge” of the ethnic other, when intersecting with imperial language of triumphalism, would often produce a distinct way of inscribing conquest on the foreign female body. I will discuss the intertwining of Roman ideology and “pornography” of conquest, ethnically framed sexual violence (from the point of view of either the victims or, in some cases, the perpetrators), and the way in which outgroup perceptions participated in the Imperial-era “rape culture”.
Ancient Rape Cultures: Sexual Violence in the Greek, Roman, Jewish, and Early Christian World